The effects of gesture and action training on the retention of math equivalence - Kersey, Alyssa J.; Carrazza, Cristina; Novack, Miriam A.; Congdon, Eliza L.; Wakefield, Elizabeth M.; Hemani-Lopez, Naureen; Goldin-Meadow, Susan (Frontiers in Psychology, 2024)
Hand gestures and actions-with-objects (hereafter ‘actions’) are both forms of movement that can promote learning. However, the two have unique affordances, which means that they have the potential to promote learning in different ways. In two studies, we compare how children learn, and importantly retain, information after performing gestures, actions, or a combination of the two during instruction about mathematical equivalence. We also ask whether individual differences in children’s understanding of mathematical equivalence (as assessed by spontaneous gesture before instruction) impacts the effects of gesture- and action-based instruction. In Study 1, which directly compares learning and retention through action and gesture, we find that, regardless of individual differences in pre-test understanding of mathematical equivalence, children learn from both action and gesture, but gesture-based instruction promotes retention better than action-based instruction. In Study 2, we ask whether using action instruction before or after gesture instruction can improve learning outcomes. Here, we find individual differences. Children who produced relatively few types of problem-solving strategies (as assessed by their gestures and speech) at pre-test performed better when they received action training immediately before gesture training than when they received action training after gesture training. In contrast, children who expressed many types of strategies (some only in gesture), and thus had a better grasp of mathematical equivalence prior to instruction, performed equally well with both orders. These results demonstrate that action training, followed by gesture, can be a useful stepping-stone in the initial stages of learning mathematical equivalence, and that gesture training can help learners retain what they learn.